(untitled) (Conference Zone, 2022)
Children with disabilities are in great need of social protection, help and support as a social support. The state and the society will protect the rights and interests of this category of children, provide material and moral support, create a legal framework, improve the infrastructure, introduce allowances, payments and benefits so that they can enjoy equal opportunities with other children. Among them, the role and importance of creating a system of social institutions that help the interests of children with disabilities, their formation and development as individuals, and ensuring their active operation is incomparable.